Aligned Boron Nitride studies using HiPIMS - Lim, Nicholas Jian Chao (2019)
Boron Nitride nanosheets are highly demanded in the materials industry due to its unique characteristic. Hexagonal Boron Nitride layered structure is lubricative yet strong and stable. It is highly insulative and able to withstand high temperature. All these properties are similar to graphene. Thus, scientists are finding the best method in producing h-BN with the highest quality and lowest cost. One of the best methods of late is the use of HiPIMS (High Power Impulse Magnetron Sputtering). HiPIMS is a physical vapor deposition method that utilizes high energy short impulse to create plasma that will aid the sputtering effect with the best yield and productivity. This project is to study the effects of the production of h-BN using HiPIMS. The films will then be analysed by the usage of a Fourier Transform Infrared spectrometer to check for product quality.